2020
DOI: 10.3390/ma13163563
|View full text |Cite
|
Sign up to set email alerts
|

An Estimation Approach for the Effective Elastic Modulus of Lightweight Bulk Filling Material with Compressible Inclusions and Imperfect Interfaces

Abstract: In this study, an approach is developed to estimate the density and effective elastic modulus of a lightweight bulk filling material made up of expanded polystyrene (EPS) and cement-reinforced clay (matrix). First, a representative volume element (RVE) is composed of cell A (an EPS and matrix) and cell B (matrix only). Then, an elastic interface is introduced to describe the discontinuity of displacement at the interface between EPS beads and matrix. Third, an Eshelby compliance tensor is modified in cell A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…Wang and Li et al [49,50] conducted a series of triaxial tests on EPS-cement lightweight clay, and found that increasing EPS bead content will also reduce the effective elastic modulus and compressive strength of this lightweight bulk filling material. However, these conclusions are at odds with the results of some studies [22][23][24][25].…”
Section: Discussion On the Strength Of Anchoring Agentsmentioning
confidence: 99%
“…Wang and Li et al [49,50] conducted a series of triaxial tests on EPS-cement lightweight clay, and found that increasing EPS bead content will also reduce the effective elastic modulus and compressive strength of this lightweight bulk filling material. However, these conclusions are at odds with the results of some studies [22][23][24][25].…”
Section: Discussion On the Strength Of Anchoring Agentsmentioning
confidence: 99%
“…Эти оценки зависят от корреляционных функций, однако полный набор пространственных корреляционных функций, необходимых для вычисления эффективных свойств, как правило, не определен. Среди последних работ также можно выделить микромеханический подход, основанный на комбинировании тензора вкладов в жесткость материала и схем гомогенизации Мори-Танака и Максвелла [36]; новый метод определения макроскопических упругих констант композитов на основе гипотезы эквивалентности полной упругой энергии [37,38]; полуаналитическую модель описания представительного объема как ансамбля ячеек с различными свойствами и несовершенными границами раздела ячеек [39].…”
Section: Introductionunclassified
“…Recently, the effect of interfacial damage on the effective elastic modulus of spherical-particle-reinforced composites has been investigated based on the linear-spring model by Yanase and Ju [ 27 ]. Further, many other theoretical models concentrate on the interface between inclusions and the matrix [ 28 , 29 , 30 , 31 , 32 , 33 ]. The microcapsules have a multilayer microstructure [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%